Research on Stock Returns Based on CAPM and Three Factor Model -- Taking the Real Estate Industry in China as an Example. - ZHANG, MIN (2020)
With the continuous development of the financial world, the status of asset pricing model is more and more prominent. To correctly determine the reasonable pricing of assets has become the content of scholars' continuous attention and research. With the reform of equity splitting and the opening of the New Third Board, a series of measures have made China's stock market more market oriented. However, due to the differences between the development of China and the western stock market, whether the asset pricing theory based on the western market is also applicable to China has become a problem faced by the Chinese stock market. Based on the empirical research on the stock data of China's A-share real estate industry in the past five years, this paper finds that the size factor, market factor, and book-to-market value ratio factor have a certain explanatory effect on the stock return rate in the Chinese real estate industry, determine the feasibility of the three-factor model in specific industries in China, and its explanatory power is better than the capital asset pricing model. The research of this paper can enrich the case of empirical research on asset pricing theory and provide valuable investment advice for investors. At the same time, the future research direction is also clarified. Based on China's unique national conditions and actual conditions, continuously exploring and researching asset pricing models that are more suitable for China's capital market.